Assessment of the Protection of Dopaminergic Neurons by an α7 Nicotinic Receptor Agonist, PHA 543613 Using [18F]LBT-999 in a Parkinson’s Disease Rat Model - Sérrière, Sophie; Doméné, Aurélie; Vercouillie, Johnny; Mothes, Céline; Bodard, Sylvie; Rodrigues, Nuno; Guilloteau, Denis; Routier, Sylvain; Page, Guylène; Chalon, Sylvie (Frontiers in Medicine, 2015)
The inverse association between nicotine intake and Parkinson’s Disease (PD) is well established and suggests that this molecule could be neuroprotective through anti-inflammatory action mediated by nicotinic receptors, including the α7-subtype (α7R). The objective of this study was to evaluate the effects of an agonist of α7R, PHA 543613, on striatal dopaminergic neurodegeneration and neuroinflammation in a rat model of PD induced by 6-hydroxydopamine (6-OHDA) lesion. Adult male Wistar rats were lesioned in the right striatum and assigned to either the PHA group (n=7) or the Sham group (n=5). PHA 543613 hydrochloride at the concentration of 6 mg/kg (PHA group) or vehicle (Sham group) was intra-peritoneally injected 2 hours before 6-OHDA lesioning and then at days 2, 4 and 6 post-lesion. Positron emission tomography (PET) imaging was performed at 7 days post-lesion using [18F]LBT-999 to quantify the striatal dopamine transporter (DAT). After PET imaging, neuroinflammation was evaluated in same animals in vitro through the measurement of the microglial activation marker 18 kDa translocator protein (TSPO) by quantitative autoradiography with [3H]PK-11195. The DAT density reflecting the integrity of dopaminergic neurons was significantly decreased while the intensity of neuroinflammation measured by TSPO density was significantly increased in the lesioned compared to intact